Marlborough's America - Webb, Stephen Saunders, 1937- (Lewis Walpole series in eighteenth-century culture and history., 2013)
Scholars of British America generally conclude that the early 18th-century Anglo-American empire was commercial in economics liberal in politics, and parochial in policy, somnambulant in an era of 'salutary neglect', but, in this book, Stephen Saunders Webb demonstrates that the American provinces, under the spur of war, became capitalist, coercive, and aggresive.